2003
DOI: 10.1038/nature01776
|View full text |Cite
|
Sign up to set email alerts
|

Post-earthquake ground movements correlated to pore-pressure transients

Abstract: Large earthquakes alter the stress in the surrounding crust, leading to triggered earthquakes and aftershocks. A number of time-dependent processes, including afterslip, pore-fluid flow and viscous relaxation of the lower crust and upper mantle, further modify the stress and pore pressure near the fault, and hence the tendency for triggered earthquakes. It has proved difficult, however, to distinguish between these processes on the basis of direct field observations, despite considerable effort. Here we presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
386
4
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 487 publications
(426 citation statements)
references
References 24 publications
19
386
4
1
Order By: Relevance
“…Poroelastic deformation was most clearly observed after two moderate earthquakes in Iceland in June 2000 (Jonsson et al, 2003), where independent observations from hydrothermal water wells could confirm that water was flowing. During the earthquakes, the water level rose in wells that were in regions around the fault that contracted, and dropped in wells that were in regions that dilated.…”
Section: Wright: Bullerwell Lecturementioning
confidence: 88%
“…Poroelastic deformation was most clearly observed after two moderate earthquakes in Iceland in June 2000 (Jonsson et al, 2003), where independent observations from hydrothermal water wells could confirm that water was flowing. During the earthquakes, the water level rose in wells that were in regions around the fault that contracted, and dropped in wells that were in regions that dilated.…”
Section: Wright: Bullerwell Lecturementioning
confidence: 88%
“…Step-like changes of groundwater level in the near field of an earthquake can often be quantitatively explained by the poroelastic pressure response to the earthquake's static strain field (Wakita 1975;Quilty & Roeloffs 1997;Jonsson et al 2003). However, the static strain mechanism can hardly explain groundwater level changes in the intermediate or far field.…”
mentioning
confidence: 99%
“…This result indicates that the effects of near-surface groundwater and pore-fluid flow driven by elastic deformation (e.g. Jónsson et al, 2003) would be too small to explain the observed trends because changes in fluid density are at most of the same order of magnitude as the elastic volumetric changes. The gravity changes estimated by the model of Ogawa and Heki (2007), which is based on elastic deformation, also turned out to be too small.…”
Section: Volumetric Changes In the Crust Due To The Slow Slip Eventmentioning
confidence: 70%